Organic molecular and inorganic isotope records of Cenozoic topography, ecosystem and climate evolution of the Southern Central Andes - Hren, Michael (2020)
The Andes are part of the longest mountain range on earthand their evolution has influenced global climate,weathering, and ecosystems since the Cretaceous. Weanalyzed the distribution and δ2H and δ13C of plant-derivedorganic biomarkers, the δ2H of volcanic glass, and thedistribution of soil-derived glycerol dialkyl glyceroltetraethers from Cenozoic sediments in the Malargüe Basinof Argentina (~35°S). Organic molecular and inorganic datawere measured to reconstruct Cenozoic changes inprecipitation isotopes, temperature, moisture deficit, andecosystems on the eastern flank of the Southern CentralAndes. Two variables (precipitation isotopes andtemperature) are strongly related to the topography of anorogen through isotopic distillation of precipitation duringrainout and changes in temperature with elevation.However, molecular biomarkers also provide keyinformation about climate and aridity through time. Weshow that organic biomarker and volcanic glass δ2H datafrom the Malargüe basin record late Cenozoic reduction oforographic lifting of airmasses associated with localdowndrop of the basin. In addition, molecular data reflectlong-term shifts in moisture deficit and plant water stressthat are consistent with regional patterns of changingclimate and aridity due to late Cenozoic cooling. Soilderivedtetraether lipid records mirror the patterns observedin organic molecular and inorganic isotope data, yet recordtemperatures that are unrealistic. These data highlight thecomplexity of universally applying the soil GDGT proxy toall terrestrial systems. In total, combined organic andinorganic data highlight the importance of multi-proxyrecords to produce a coherent representation of long-termecosystem and climate change in a region impacted byevolving climatic and tectonic boundary conditions.